Media Pembelajaran Pengenalan Nama Buah Menggunakan Macromedia Flash 8 Di TK Ulul Ilmi Kecamatan Sidamanik Kota Pematang Siantar - Ikhwan, Ali; Toar, Miftahul Jannah; Barus, Ananda Br; Hafidz, Sefian Habil; Ritonga, Satria Habibi (CV. Information Technology Training Center - Indonesia (ITTC), 2023)
This study discusses the design and manufacture of Learning Multimedia Applications to Know Fruit Names Based on Macromedia Flash 8 Applications in Ulul Ilmi Kindergarten, Sidamanik District, Pematang Siantar City. The delivery of learning material for the introduction of fruit names in scientific kindergarten still seems monotonous. In his learning, the teacher only relies on books, pictures, and oral media. Not relying on effective learning media and attracting more students' attention by utilizing technological developments through multimedia-based PCs/Laptops. Making this Fruit Name Recognition Multimedia Application using macromedia flash 8-based software. The development of this application uses the media waterfall which starts from needs analysis to system implementation and maintenance. This application helps students to be more expressive in knowing the names of fruits, by displaying pictures of fruit and leading to learning quizzes. Based on the trial results, this application can run well on multimedia-based devices with the Macromedia Flash 8 version.